Living Fiqh Munakahat In Practice: Negotiating Islamic Marriage Law in Indonesia and Thailand - Wahyu Abdul Jafar (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
This study examines the dynamics of Islamic marriage law in Indonesia and Thailand through the perspective of Living Fiqh Munakahat, emphasizing how Islamic legal norms are negotiated, adapted, and practiced within diverse socio-political contexts. Rather than framing the issue solely as a legal implementation problem, this research explores the interaction among state law, religious authority, and social practices in shaping marriage institutions. This study employs a library research method, using documentation techniques and qualitative descriptive analysis, and ensures data validity through source triangulation. The findings reveal that Islamic family law operates not merely as a formal legal system but as a living normative framework embedded in everyday social life. In Thailand, where Muslims constitute a minority, Islamic marriage law functions as a flexible and negotiated system, often serving as a mediating tool between the Buddhist-majority state and Muslim religious authorities. Its application remains optional and is geographically limited to the southern provinces of Pattani, Narathiwat, Yala, and Satun, reflecting a localized, community-based legal practice. In contrast, Indonesia institutionalizes Islamic marriage law as a binding legal framework applicable to all Muslims, supported by both formal and material legal provisions. Furthermore, differences in institutional arrangements—such as the absence of specialized Islamic courts in Thailand and the mandatory pre-marital courses enforced through social sanctions—demonstrate how legal norms are shaped by local needs and state structures. From a Living Fiqh Munakahat perspective, these variations indicate that Islamic marriage law is continuously reinterpreted and negotiated, transforming from a static body of norms into a dynamic social practice. This study highlights that the implementation of Islamic marriage law should be understood as an ongoing process of negotiation between text, context, and authority within plural legal systems. Penelitian ini mengkaji dinamika hukum perkawinan Islam di Indonesia dan Thailand melalui perspektif Living Fiqh Munakahat, dengan menekankan bagaimana norma-norma hukum Islam dinegosiasikan, disesuaikan, dan dipraktikkan dalam berbagai konteks sosial-politik yang berbeda. Penelitian ini tidak hanya melihat persoalan tersebut sebagai masalah penerapan hukum semata, tetapi juga mengkaji hubungan antara hukum negara, otoritas agama, dan praktik sosial dalam membentuk lembaga perkawinan. Penelitian ini menggunakan metode studi kepustakaan dengan teknik dokumentasi dan analisis deskriptif kualitatif, serta memastikan keabsahan data melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa hukum keluarga Islam tidak hanya berfungsi sebagai sistem hukum formal, tetapi juga sebagai kerangka nilai yang hidup dan melekat dalam kehidupan sosial sehari-hari. Di Thailand, di mana umat Islam merupakan kelompok minoritas, hukum perkawinan Islam bersifat lebih fleksibel dan hasil negosiasi, serta sering menjadi jembatan antara negara yang mayoritas Buddha dan otoritas keagamaan Islam. Penerapannya bersifat terbatas dan hanya berlaku di empat provinsi selatan, yaitu Pattani, Narathiwat, Yala, dan Satun, sehingga lebih bersifat lokal dan berbasis komunitas. Sebaliknya, di Indonesia, hukum perkawinan Islam dilembagakan sebagai hukum yang mengikat bagi seluruh umat Islam, dengan dukungan aturan hukum formal dan material. Selain itu, terdapat perbedaan kelembagaan, seperti tidak adanya pengadilan agama khusus di Thailand serta adanya kursus pra-nikah yang wajib dan disertai sanksi sosial, yang menunjukkan bahwa hukum dibentuk sesuai kebutuhan lokal dan struktur negara. Dari perspektif Living Fiqh Munakahat, perbedaan ini menunjukkan bahwa hukum perkawinan Islam terus ditafsirkan dan dinegosiasikan, sehingga berubah dari sekadar aturan yang statis menjadi praktik sosial yang dinamis. Penelitian ini menegaskan bahwa pelaksanaan hukum perkawinan Islam harus dipahami sebagai proses negosiasi yang terus berlangsung antara teks, konteks, dan otoritas dalam sistem hukum yang plural.